Sweet syndrome: A retrospective study of 64 cases and proposal of an algorithmic approach to improve investigation and management - N. H. Gopee; F. G. Charlton; P. J. Hampton (Wiley, 2021)
Abstract Background Sweet syndrome (SS) can be categorized as classical Sweet syndrome (CSS), malignancy‐associated Sweet syndrome (MASS) or drug‐induced Sweet syndrome (DISS). Appropriate categorization of patients with SS and identification of the associated trigger are essential to direct subsequent investigations and follow‐up, especially given that 21% of cases are malignancy‐associated. However, no published guidelines exist to guide this. Objective To analyse the categorization, management and outcomes of patients with SS in order to propose a structured approach for investigation and follow‐up. Methods Retrospective data collection from the electronic records of patients diagnosed with SS between 1 January 2005 and 31 December 2018. Categorized and non‐categorized patients were compared, and the yield rate of investigations and duration of follow‐up were analysed. Results Sixty‐four patients were included with CSS (77%), MASS (20%) and DISS (3%). Of these, 34 (53%) cases were not categorized by the assessing clinicians, three of which were subsequently diagnosed with a malignancy, up to 19 months later. There was no significant difference in investigations performed between categorized and non‐categorized patients and the yield rates were modest overall. Follow‐up averaged 10.5 (16.8) months; non‐categorized patients were followed‐up for significantly longer than categorized patients (15.0 (21.2) vs. 5.4 (6.8) months, p < 0.05). Conclusion The lack of a structured way to approach patients with SS can lead to under‐ or over‐investigation, diagnostic delays of underlying conditions and unnecessary follow‐up. An algorithm is proposed to identify the likely trigger and manage patients accordingly. Larger prospective studies are required to confirm the optimal approach to investigate and follow‐up patients with SS.